Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kepatuhan Konsumsi Tablet Besi (FE) di Puskesmas Martoba Pematang Siantar Tahun 2023 - Berliana Dwi Sari Purba; Adelina Sembiring; Mastaida Tambun (Pusat Riset dan Inovasi Nasional, 2024)
The cause of most anemia in Indonesia is a lack of iron which is needed for the formation of hemoglobin. Anemia in pregnant women brings consequences and complications that have a high risk of miscarriage, bleeding, LBW, uterine atony, uterine inertia, placental retention. The incidence of anemia in Indonesia is increasing because anemia treatment is carried out when women are pregnant rather than starting before pregnancy. The aim of the research is to determine the relationship between knowledge and attitudes of pregnant women and compliance with consuming iron (Fe) tablets at the Martoba Pematang Siantar Community Health Center in 2023.This research uses analytical observational research, the sample in the research is 52 people using Total Sampling. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square The results of the cross-tabulation research show a relationship between attitudes and compliance with consuming iron (Fe) tablets at the Martoba Pematang Siantar Community Health Center in 2023 with a P value of 0.020 (P value <0.005), so Ho is rejected and Ha is accepted.Suggestions for midwifery services to provide education to increase mothers' knowledge about basic immunization.